2015
DOI: 10.1038/ng.3390
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance estimation with imputed variants finds negligible missing heritability for human height and body mass index

Abstract: We propose a method (GREML-LDMS) to estimate heritability for human complex traits in unrelated individuals using whole-genome sequencing (WGS) data. We demonstrate using simulations based on WGS data that ~97% and ~68% of variation at common and rare variants, respectively, can be captured by imputation. Using the GREML-LDMS method, we estimate from 44,126 unrelated individuals that all ~17M imputed variants explain 56% (s.e. = 2.3%) of variance for height and 27% (s.e. = 2.5%) for body mass index (BMI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
876
6
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 771 publications
(932 citation statements)
references
References 37 publications
45
876
6
5
Order By: Relevance
“…Additionally, the field of epistasis, that is the interaction of different genes, is rapidly evolving. Finally, it has been shown for other complex disorders that the combined small effects of hundreds of thousands of SNPs may jointly explain the currently poorly understood inheritance patterns (Yang et al , 2015). The results achieved thus far do, however, provide valuable insight into the pathophysiology of CAD and MI and are starting points for individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the field of epistasis, that is the interaction of different genes, is rapidly evolving. Finally, it has been shown for other complex disorders that the combined small effects of hundreds of thousands of SNPs may jointly explain the currently poorly understood inheritance patterns (Yang et al , 2015). The results achieved thus far do, however, provide valuable insight into the pathophysiology of CAD and MI and are starting points for individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from imputed genotype data for height implies that more additive genetic variation is explained by variants with MAF < 10% than expected under an evolutionary neutral model, consistent with purifying selection of the height-associated loci. 49 In the near future, when additive genetic variance will be estimated from WGS data in large samples, the contribution of observed rare and low-frequency variants will be estimated explicitly. Estimates from data available to date provide the first evidence for different genetic architectures between diseases, 50 for example, there is more signal from rare variants for amyotrophic lateral sclerosis (motor neuron disease [MIM: 105400]) than for schizophrenia 51 and more predicted loci for schizophrenia than for immune disorders 52 and hypertension.…”
Section: Pleiotropy Is Pervasivementioning
confidence: 99%
“…Yang et al [26] found that imputed genome sequence explained 50% of the phenotypic variance for height. Sequence variants with MAF , 0.1 explained more variance than other MAF classes despite the fact that they were not accurately imputed.…”
Section: Genetic Architecture Of Complex Traitsmentioning
confidence: 99%
“…Their allele frequencies are biased towards low MAF compared with a neutral model, but only slightly. That is, most of the variance is due to common variants [26].…”
Section: Genetic Architecture Of Complex Traitsmentioning
confidence: 99%